Coerência na representação temática de artigos científicos indexados no repositório de saúde pública da Fundação Oswaldo Cruz - Santos, Fatima Cristina Lopes dos (2017)
This dissertation investigates the semantic coherence in the indexing of journal articles in the public health area, in Portuguese, indexed in the Scientific Production Repository of the National School of Public Health Sergio Arouca (ENSP) of the Oswaldo Cruz Foundation (Fiocruz), aiming to contribute With the semantic interoperability between the repositories of this Foundation. The research is based on the theoretical and methodological assumptions of the areas of thematic representation and documentary linguistics, within the scope of the Organization of Knowledge in CI, as well as in Bibliometrics, and its goals are: (a) to verify comparatively the semantic coherence in the indexing of articles Scientists in the field of public health; (B) to investigate the occurrence of indexation terms in light of quantitative bibliometric models used in indexing in Information Science; (C) provide evidence of the importance of the discursive genre scientific journal article in the area of public health; (D) identify the terms-figure and background terms of the articles analyzed for a better understanding of the informativeness of scientific texts; (E) contribute to the advancement of knowledge about phenomena that guide the indexing of scientific information, particularly on semantic coherence in indexing information in the health area. For that, 10 articles from Brazilian scientific journals, published in open access between 2012-2014 and registered in the Scientific Production Repository of the ENSP / Fiocruz, were analyzed. The articles were processed in the software RankWord and WordSmith 6.0, applying later the laws of Zipf and Goffman Transition Point to identify the terms of high semantic load of the texts. The terms selected in each article were compared in the 5 (five) indicators used in the research: Goffman Region T; Expressions WordSmith 6.0, Keywords; DeCS (Descriptors in Health Sciences) and Title. The results were compiled using the discourse plan of the sentences, with emphasis on terms used as foregrounding and in terms used as background, helping to verify the degree of coherence between the articles. The data collected reveal a low degree of semantic coherence in most articles studied. We suggest an investigation with an expanded sample to confirm the data obtained, especially when dealing with articles published in Portuguese in the health area and its importance in national scientific communication.